Narrative approach as a medium for Sejahtera student mentality at the Centre for Foundation Studies, IIUM - Mohd. Basri, Mohd. Rafaei; Aling, Noor Asiah; Ismail, Nur Farrah Syazwanie; Saidin, Nurhafizah; Mohd. Ali, Noor Saadiah (Nungemilang Enterprise, 2023)
The Institute for Public Health’s National Health and Morbidity Survey 2022 found that problems among Malaysian youths have alarmingly increased. According to the research, one in every eight teenagers had considered suicide, growing from 10.0% in 2017 to 13.1% in 2022; one in ten teenagers had attempted suicide, increasing from 6.9% in 2017 to 9.5% in 2022; and one in four felt depressed. This growing trend on mental health problems has been growing progressively since 2012. Hence, the study explores an integrated and supplementary approach in promoting positive mental health at the Centre for Foundation Studies, IIUM. The proposed qualitative narrative analysis/approach integrates the practice of narration of Quranic and Islamic stories on selected exemplary figures with the normal orientation programmes. A non-probability sampling technique i.e., voluntary sampling, is employed for sample collection i.e., 2596 (students) and 46 (staff). The respondents are given 2 different sets of questionnaires: consisting of 8 questions for students and 11 questions for the staff. The questionnaires cover 7 constructs or areas of study and employ 5 -point Likert scale measurement. The responses from the respondents are analysed quantitatively to get the average (mean) Sentiment score for each construct. The analyses of the responses indicate that the overall acceptance of 4.41 Sentiment score, with 4.40 Sentiment score on relevancy of the approach used and the comprehension level. The study concludes that the narrative approach is well-accepted as a medium promoting healthy mentality, while also highlighting the requirements of proper training and organisation of the module.